Metode Role Playing: Strategi Aktif untuk Meningkatkan Pembelajaran Pendidikan Pancasila - Siska Damayanti, Ni Wayan; Sukadi; Budiarta, I Wayan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
Abstract The quality of education is largely determined by the quality of managers and educators, where teachers have a central role as professionals who are responsible for designing, implementing, and evaluating the learning process. This study uses the method library research or literature study, namely by collecting data through various relevant literature sources. The purpose of this study is to determine the steps for implementing the method role playing in learning Pancasila Education and analyzing its strengths and weaknesses, Teacher professionalism is a key factor in improving the quality of education, especially through the application of innovative learning methods that are in accordance with student needs. In this context, teachers are required to be able to choose an effective approach to create an active and meaningful learning atmosphere. One method that is considered relevant to be applied in learning Pancasila Education is role playing. This method allows students to play a role and interact directly in simulated situations, thereby fostering a more concrete understanding of Pancasila values so that it can provide a more comprehensive picture of the effectiveness of the method in supporting learning objectives. Keywords: Learning Methods, Role Playing, Pancasila Education